2015
DOI: 10.1111/apt.13265
|View full text |Cite
|
Sign up to set email alerts
|

Occult vs. overt upper gastrointestinal bleeding – inverse relationship and the use of mucosal damaging and protective drugs

Abstract: SUMMARY BackgroundWhile efforts have focused on the prevention of overt upper gastrointestinal bleeding (UGIB), little is known about occult GIB, which might also originate from sites not protected by acid inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…As a result of effective acidinhibiting drugs, the incidence of upper gastrointestinal bleeding has decreased.1-3,6 By contrast, diagnosis of ulcers and erosions of the small bowel among individuals taking aspirin and NSAIDs has increased; these patients have few treatment options because prostaglandin production (rather than excess acid) is the primary driver of ulcer pathogenesis in the alkaline environment of the small bowel. [3][4][5][6][7][8][9][10][11]14,15 Since aspirin and NSAIDs are known to cause ulcers by suppressing mucosal prostaglandin synthesis,3-11 we chose to include patients taking these drugs in our study. These factors highlight the importance of identifying a drug that can be used to heal small bowel ulcers in patients who take aspirin and NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As a result of effective acidinhibiting drugs, the incidence of upper gastrointestinal bleeding has decreased.1-3,6 By contrast, diagnosis of ulcers and erosions of the small bowel among individuals taking aspirin and NSAIDs has increased; these patients have few treatment options because prostaglandin production (rather than excess acid) is the primary driver of ulcer pathogenesis in the alkaline environment of the small bowel. [3][4][5][6][7][8][9][10][11]14,15 Since aspirin and NSAIDs are known to cause ulcers by suppressing mucosal prostaglandin synthesis,3-11 we chose to include patients taking these drugs in our study. These factors highlight the importance of identifying a drug that can be used to heal small bowel ulcers in patients who take aspirin and NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] We previously found that the annual incidence of occult or obscure gastrointestinal bleeding among individuals in southwest Scotland increased from 243·1 per 100 000 individuals in 2007, to 292·8 per 100 000 individuals in 2012, and the corresponding incidence of upper gastrointestinal bleeding decreased from 140·1 per 100 000 individuals in 2007, to 88·0 per 100 000 individuals in 2012. 6 These changes were associated with an increase in the number of prescriptions of non-steroidal anti-inflammatory drugs (NSAIDs), aspirin, and proton-pump inhibitors between 2007 and 2012. 6 Obscure gastrointestinal bleeding mainly originates from the small bowel, and its incidence has been rising, which might be explained by the widespread use of low-dose aspirin and NSAIDs.3- 6 The diagnosis of small bowel ulcers in patients taking these drugs has been facilitated by the introduction of video capsule endoscopy.7-9 Small bowel ulcers develop as a result of the suppression of mucosal prostaglandin synthesis by aspirin or NSAIDs,7-9 and because of the alkaline environment of the small bowel, these ulcers do not respond to acid inhibitors.7 A pilot study10 found that small bowel mucosal lesions associated with aspirin use healed following treatment with misoprostol (a prostaglandin analogue) in four of seven patients.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations